Hadith #156 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
I said: Messenger of Allah, which of the deeds is the best? He (the Holy Prophet) replied: Belief in Allah and Jihad in His cause. I again asked: Who is the slave whose emancipation is the best? He (the Holy Prophet) replied: One who is valuable for his master and whose price is high. I said: If I can’t afford to do it? He (the Holy Prophet) replied: Help an artisan or make anything for the unskilled (labourer). I (Abu Dharr) said: Messenger of Allah, you see that I am helpless in doing some o
Grade: Sahih

Hadith #179 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
I came to the Apostle (may peace be upon him ) and he was asleep with a white mantle over him. I again came, he was still asleep, I came again and he had awakened. I sat by his side and (the Holy Prophet) observed: There is none among the bondsmen who affirmed his faith in La illaha ill-Allah there is no God but Allah) and died in this state and did not enter Paradise. I (Abu Dharr) said: Even if he committed adultery and theft? He (the Holy Prophet) replied: (Yes) even though he committed adult
Grade: Sahih

Hadith #200 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Three are the persons with whom Allah would not speak on the Day of Resurrection: the bestower of gift who does not give anything but by laying obligation on him, the seller of goods who sells them by taking false oath and one who hangs low his lower garment.
Grade: Sahih

Hadith #304 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Do you know where the sun goes? They replied: Allah and His Apostle know best. He (the Holy Prophet) observed: Verily it (the sun) glides till it reaches its resting place under the Throne. Then it falls prostrate and remains there until it is asked: Rise up and go to the place whence you came, and it goes back and continues emerging out from its rising place and then glides till it reaches its place of rest under the Throne and falls prostrate and remains in that state until it is asked: Rise u
Grade: Sahih

Hadith #305 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Do you know where the sun goes? The remaining part of the hadith is the same.
Grade: Sahih

Hadith #306 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
I entered the mosque and the Messenger of Allah (ﷺ) was sitting there. When the sun disappeared (from the sight) he said: O Abu Dharr! Do you know where it goes? He (the narrator) said: Allah and His Apostle know best. He (the Holy Prophet) said. Verily it goes and begs permission, for prostration (to Allah) and the permission is granted to it. Once it would be said: Return to the place whence you came, and then it would rise from its setting place. Then he, after the recitation of ‘Abdullah
Grade: Sahih

Hadith #307 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
I asked the Messenger of Allah (ﷺ) the (implication of the) words of Allah, the Exalted: The sun glides to its appointed resting place. He replied: Its appointed resting place is under the Throne.
Grade: Sahih

Hadith #348 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
I asked the Messenger of Allah (ﷺ): Did you see thy Lord? He said: (He is) Light; how could I see Him?
Grade: Sahih

Hadith #373 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
I know the last of the inhabitants of Paradise to enter it and the last of the inhabitants of Hell to come out of it. He is a man who would be brought on the Day of Resurrection and it will be said: Present his minor sins to him, and withhold from him his serious sins. Then the minor sins would be placed before him, and it would be said: On such and such a day you did so and so and on such and such a day you did so and so. He would say: Yes. It will not be possible for him to deny, while he woul
Grade: Sahih

Hadith #1039 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
The Messenger of ‘Allah (ﷺ) said: When any one of you stands for prayer and there is a thing before him equal to the back of the saddle that covers him and in case there is not before him (a thing) equal to the back of the saddle, his prayer would be cut off by (passing of an) ass, woman, and black Dog. I said: O Abu Dharr, what feature is there in a black dog which distinguish it from the red dog and the yellow dog? He said: O, son of my brother, I asked the Messenger of Allah (ﷺ) as you
Grade: Sahih

Hadith #1063 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
I said: Messenger of Allah, which mosque was set up first on the earth? He said: Al-Masjid al-Haram (the sacred). I (again) said: Then which next? He said: It was the Masjid Aqsa. I (again) said: How long the space of time (between their setting up)? He (the Holy Prophet) said: It was forty years. And whenever the time comes for prayer, pray there, for that is a mosque; and in the hadith transmitted by Abu Kamil (the words are):” Whenever time comes for prayer, pray, for that is a mosque (for
Grade: Sahih

Hadith #1133 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
The Apostle of Allah (ﷺ) said: The deeds of my people, good and bad, were presented before me, and I found the removal of something objectionable from the road among their good deeds, and the sputum mucus left unburied in the mosque among their evil deeds.
Grade: Sahih

Hadith #1296 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
The Mu’adhdbin (the announcer of the hour of prayer) of the Messenger of Allah (ﷺ) called for the noon prayer. Upon this the Messenger of Allah (ﷺ) said: Let it cool down, let it cool down, or he said: Wait, wait for the intensity of heat is from the exhalation of Hell. When the heat is intense, delay the prayer till it becomes cooler. Abu Dharr said: (We waited) till we saw the shadow of the mounds.
Grade: Sahih

Hadith #1360 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
The Messenger of Allah (ﷺ) said to me: How would you act when you are under the rulers who would delay the prayer beyond its prescribed time, or they would make prayer a dead thing as far as its proper time is concerned? I said: What do you command? He (the Holy Prophet) said: Observe the prayer at Its proper time, and if you can say it along with them do so, for it would be a superetogatory prayer for you. Khalaf (one of the narrators in the above hadith) has not mentioned” beyond their (pr
Grade: Sahih

Hadith #1361 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
The Messenger of Allah (ﷺ) said to me: O Abu Dharr, you would soon find after me rulers who would make their prayers dead. You should say prayer at its prescribed time. If you say prayer at its prescribed time that would be a supererogatory prayer for you, otherwise you saved your prayer.
Grade: Sahih

Hadith #1362 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
My friend (the Holy Prophet) bade me to hear and obey (the ruler) even if he is a slave having his feet and arms cut off, and observe prayer at its prescribed time. (And further said): It you find people having observed the prayer, you in fact saved your prayer, otherwise (if you join with them) that would be a Nafl prayer for you.
Grade: Sahih

Hadith #1363 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
The Messenger of Allah (ﷺ) struck my thigh and said: How would you act if you survive among the people who would delay prayers beyond their (prescribed) time? He (Abu Dharr) said: What do you command (under this situation)? He (the Holy Prophet) slid: Observe prayer at its prescribed time, then go (to meet) your needs, and if the Iqama is pronounced, and you are present in the mosque, then observe prayer (along with the Jama’at).
Grade: Sahih

Hadith #1365 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
(The Messenger of Allah) said: How would you, or how would thou, act if you survive to live among people who defer prayer beyond the (prescribed) time? (The narrator said: Allah and His Messenger know best). whereupon he said: Observe prayer at its prescribed time, but if the Iqama is pronounced for (congregational) prayer, then observe prayer along with them. for herein is an excess of virtue.
Grade: Sahih

Hadith #1565 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
In the morning charity is due from every bone in the body of every one of you. Every utterance of Allah’s glorification is an act of charity. Every utterance of praise of Him is an act of charity, every utterance of profession of His Oneness is an act of charity, every utterance of profession of His Greatness is an act of charity, enjoining good is an act of charity, forbidding what is distreputable is an act of charity, and two rak’ahs which one prays in the forenoon will suffice.
Grade: Sahih

Hadith #2184 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
I went to the Messenger of Allah (ﷺ) and he was sitting under the shade of the Ka’ba. As he saw me he said: By the Lord of the Ka’ba, they are the losers. I came there till I sat and I could not stay (longer) and (then) stood up. I said: Messenger of Allah, let my father, be ransom for you, who are they (the losers)? He said: They are those having a huge amount of wealth except so and so and (those who spend their wealth generously on them whom they find in front of them, behind them and o
Grade: Sahih

Hadith #2188 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
I walked with the Messenger of Allah (ﷺ) on the stony ground of Medina in the afternoon and we were looking at Uhud. The Messenger of Allah (way peace by upon him) said: Abu Dharr! I said: Messenger of Allah, I am here at thy beck and call. He said: What I desire is that Uhud be gold with me and three nights should pass and there is left with me any dinar but one coin which I would keep to pay debt. (I love) to spend it among the servants of Allah like this and he pointed in front of him, and
Grade: Sahih

Hadith #2189 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
I went out one night (and found) the Messenger of Allah (ﷺ) walking all alone. There was no man with him. I thought that he did not like anyone walking along with him. So I began to walk in the light of the moon. He, however turned his attention to me and saw me and said: Who is this? I said: It is Abu Dharr. Let Allah make me as ransom for you. He said: Abu Dharr, come on. He (Abu Dharr) said: So I walked along with him for some time and he said: The wealthy persons would have little (reward)
Grade: Sahih

Hadith #2213 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
some of the people from among the Companions of the Messenger of Allah (ﷺ) said to him: Messenger of Allah, the rich have taken away (all the) reward. They observe prayer as we do; they keep the fasts as we keep, and they give Sadaqa out of their surplus riches. Upon this he (the Holy Prophet) said: Has Allah not prescribed for you (a course) by following which you can (also) do sadaqa? In every declaration of the glorification of Allah (i. e. saying Subhan Allah) there is a Sadaqa, and every
Grade: Sahih

Hadith #2353 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Verily there would arise from my Ummah after me or soon after me a group (of people) who would recite the Qur’an, but it would not go beyond their throats, and they would pass clean through their religion just as the arrow passes through the prey, and they would never come back to it. They would be the worst among the creation and the creatures. Ibn Samit (one of the narrators) said: I met Rafi’ b. ‘Amr Ghifari, the brother of Al-Hakam Ghifari and I said: What is this hadith that I heard f
Grade: Sahih

Hadith #2849 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Tamattu’ in Hajj was a special concession for us.
Grade: Sahih

Hadith #2850 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Two are the Mut’as which were not permissible but only for us, i. e. temporary marriage with women and Tamattu’ in Hajj.
Grade: Sahih

Hadith #4588 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
I said to the Prophet (ﷺ): Messenger of Allah, will you not appoint me to a public office? He stroked my shoulder with his hand and said: Abu Dharr, thou art weak and authority is a trust. and on the Day of judgment it is a cause of humiliation and repentance except for one who fulfils its obligations and (properly) discharges the duties attendant thereon.
Grade: Sahih

Hadith #4622 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
My friend (i. e. the Holy Prophet) advised me to listen (to the man in position of authority) and obey (him) even if he were a slave maimed (and disabled).
Grade: Sahih

Hadith #5836 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Allah’s Messenger, what about the vessels of that Cistern? He said: By Him in Whose Hand is the life of Muhammad, the vessels would outnumber the stars in the sky and its planets shining on a dark cloudless night. These would be the vessels of Paradise. He who drinks out of it (the Cistern) would never feel thirsty. There would flow in it two spouts from Paradise and he who would drink out of it would not feel thirsty; and the distance between its (two corners) is that between ‘Amman and Ail
Grade: Sahih

Hadith #6270 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Go to your people and say that the Messenger of Allah (ﷺ) says: Ghifar (is a tribe) to whom Allah granted pardon, and Aslam (is the tribe) to whom Allah granted safety.
Grade: Sahih

Hadith #6271 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
To the tribe of Aslam Allah has granted safety and to the tribe of Ghifar Allah has granted pardon.
Grade: Sahih

Hadith #6334 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
You would soon conquer a land where people are in the habit of using foul language. They have a right of kinship upon you. And when you see two persons fighting for the space of a brick, then get out of that. He (Abu Dharr) then happened to pass by Rabila and ‘Abd al-Rahman, the two sons of Shurahbil b. Hasana, and they had been disputing for the space of a brick. So he left the land.
Grade: Sahih

Hadith #6335 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
You would soon conquer Egypt and that is a land which is known (as the land of al-qirat). So when you conquer it, treat its inhabitants well. For there lies upon you the responsibility because of blood-tie or relationship of marriage (with them). And when you see two persons falling into dispute amongst themselves for the space of a brick, than get out of that. He (Abu Dharr) said: I saw Abd al-Rahman b. Shurahbil b. Hasana and his brother Rabi’a disputing with one another for the space of a b
Grade: Sahih

Hadith #6410 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
“O My servants, I have forbidden oppression for Myself and have made it forbidden amongst you, so do not oppress one another. O My servants, all of you are astray except for those I have guided, so seek guidance of Me and I shall guide you, O My servants, all of you are hungry except for those I have fed, so seek food of Me and I shall feed you. O My servants, all of you are naked except for those I have clothed, so seek clothing of Me and I shall clothe you. O My servants, you sin by night an
Grade: Sahih

Hadith #6413 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Verily I have made oppression unlawful for Me and for My servants too, so do not commit oppression. The rest of the hadith is the same.
Grade: Sahih

Hadith #6525 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Abu Dharr, when you prepare the broth, add water to that and give that (as a present) to your neighbour.
Grade: Sahih

Hadith #6526 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Whenever you prepare a broth, add water to it, and have in your mind the members of the household of your neighbours and then give them out of this with courtesy.
Grade: Sahih

Hadith #6527 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Allah’s Apostle (ﷺ) said to me: Don’t consider anything insignificant out of good things even if it is that you meet your brother with a cheerful countenance.
Grade: Sahih

Hadith #6556 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
It was said to Allah’s Messenger (ﷺ): What is your opinion about the person who has done good deeds and the people praise him? He said: It is glad tidings for a believer (which he has received in this mortal world).
Grade: Sahih

Hadith #6668 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
” He who comes with goodness, there are in store for him ten like those and even more than those: ‘And he who comes with vice, ‘ it is only for that that he is called to account. I even forgive him (as I like) and he who draws close to Me by the span of a palm I draw close to him by the cubit, and he who draws close to Me by the cubit I draw close to him by the space (covered) by two hands, and he who walks towards Me I rush towards him, and he who meets Me in the state that his sins fill
Grade: Sahih

Hadith #6756 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Those for which Allah made a choice for His Angels and His servants (and the words are):” Hallowed be Allah and praise is due to Him.”
Grade: Sahih

Hadith #6757 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
Should I not inform you about the words liked most by Allah? I said: Allah’s Mes- senger, do inform me about the words liked most by Allah. He said: Verily, the words liked most by Allah are:” hallowed be Allah and praise is due to Him.”
Grade: Sahih

Hadith #6758 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
There is no believing servant who supplicates for his brother behind his back (in his absence) that the Angels do not say: The same be for you too.
Grade: Sahih

Hadith #7367 - Sahih Muslim - Abu Dharr al-Ghaffari (Sahih Muslim)
” These two adversaries who dispute about their Lord” (xxii. 19) was revealed in connection with those who on the Day of Badr came out (of rows to fight against the non-believers and they were) Hamza, ‘Ali, ‘Ubaida b. Harith (from the side of the Muslims) and ‘Utba and Shaiba, both of them the sons of Rabi’a and Walid b. ‘Utba (from the side of the non-believers of Mecca).
Grade: Sahih